Klippel–Feil syndrome: A very unusual cause of severe aortic regurgitation visualized by multimodality imaging. Issue 8 (27th June 2019) - Ahluwalia, Monica; Sehgal, Sankalp; Vainrib, Alan F.; Applebaum, Robert; Latson, Larry; Williams, Mathew R.; Saric, Muhamed
Abstract: A 51‐year‐old man with Klippel–Feil syndrome (KFS) and immunodeficiency syndrome, status postintravenous immunoglobulin therapy, presented with shortness of breath. He was found to have severe aortic regurgitation in the setting of a trileaflet aortic valve with thickened leaflets and mild prolapse of the right coronary cusp with left ventricular dilation and borderline left ventricular ejection fraction. Although various cardiac anomalies have been described in KPS, otherwise unexplained severe aortic regurgitation has not been previously reported to the best of our knowledge. The patient underwent an uncomplicated surgical aortic valve replacement with a 25‐mm Medtronic Avalus pericardial tissue valve resulting in symptomatic improvement. Intra‐operative management and transesophageal echocardiography can be particularly challenging in KFS patients. We describe the first reported case of severe aortic regurgitation in KPS, review the cardiac anomalies associated with the syndrome, and highlight the clinical challenges in intra‐operative management of these patients.